Self-reported knowledge and practice of interdental aids among people of Riyadh, Saudi Arabia - A cross-sectional study - Khalid Gufran; Khalid Muslih Alanazi; Abdulrhman Khalid Alanazi; Abdulmajeed Saeed Alqwiri; Faiz Mohammed Alsubaie; Nawaf Munawir Alotaibi (Wolters Kluwer Medknow Publications, 2021)
Background: Periodontal disease is a common pathological oral ailment which affects the supporting structures of the teeth. Dental plaque is one of the major causes for gingivitis and periodontitis. If left untreated, this will lead to tooth loss. Studies have shown that oral prophylaxis will reduce gingival and periodontal inflammation by removing the plaque in all the surfaces. The objective was to assess knowledge and practice of interdental aids among people of Riyadh, Saudi Arabia. Methodology: A descriptive study was conducted among people using questionnaire. Results: 96% of the subjects brushed their teeth with brush and paste. 59% of the study subjects had knowledge regarding interdental aids, whereas only 15% of them practiced it. 72% of the people mentioned that dentists gave information regarding interdental aids. Conclusions: Among the study subjects, even though there were deficits in few areas, overall knowledge about interdental aids was good and it increased with increasing level of education.